2017
DOI: 10.1080/2374068x.2017.1330842
|View full text |Cite
|
Sign up to set email alerts
|

Physical integrity of 3D printed parts for use as embossing tools

Abstract: On inception, 3D printed parts were typically used at prototyping stage to give the end user/customer a real world concept of how the part may appear when traditional manufacturing techniques were employed for final part fabrication. In this context, mechanical properties such as load bearing capacity or wear rate were not typically of primary concern. This paper investigates, given the advances in 3D printing technology, the potential for using 3D printed parts for high throughput embossing tools. The key mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…These support structures are removed from the fabricated parts using different methods, such as sonication in a sodium hydroxide solution, heating, or the use of high-pressure water jets. 50 According to previous research, mixing tripropylene glycol diacrylate (TPGDA) with triethylene glycol methyl ether (TGME), a solvent with a high boiling point, produces a sprayable support material. TGME is also an efficient addition that decreases the mechanical characteristics of the cured TPGDA structure by creating a porous structure.…”
Section: Types Of Technology For 4d Printed Smart Textilesmentioning
confidence: 99%
“…These support structures are removed from the fabricated parts using different methods, such as sonication in a sodium hydroxide solution, heating, or the use of high-pressure water jets. 50 According to previous research, mixing tripropylene glycol diacrylate (TPGDA) with triethylene glycol methyl ether (TGME), a solvent with a high boiling point, produces a sprayable support material. TGME is also an efficient addition that decreases the mechanical characteristics of the cured TPGDA structure by creating a porous structure.…”
Section: Types Of Technology For 4d Printed Smart Textilesmentioning
confidence: 99%
“…They stated that elastic modulus, strain at fracture, maximum compressive strength and yield strength of MED610 is higher than Vero White and RGD525. It was found that RGD 525 has the lowest and MED610 has the highest wear rate [ 13 ]. Kaweesa and Meisel designed fatigue test bars in which the middle sections have a material gradient transition region with continuous gradients and stepwise gradient types of functionally graded material interface designs with two materials: VeroCyan and TangoBlackPlus.…”
Section: Process and Materialsmentioning
confidence: 99%
“…Since liquid or molten material is used in MJ, a gel-like support structure is needed, especially in overhang regions. These support structures are removed from the part using different methods: sonication in a bath of sodium hydroxide solution, heating or using a high-pressure water jet [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is high-temperature opaque brittle plastic material which has been recently used in 3D printer technology, and as a model or support material as well [18]. Usually, this material needs to be treated thermally, following a specific procedure [19], in order to improve its properties by alternating it from orthotropic to isotropic material.…”
Section: Introductionmentioning
confidence: 99%